Triptolide Induces Leydig Cell Apoptosis by Disrupting Mitochondrial Dynamics in Rats - Lv, Linyan; Chang, Yajie; Li, Yanqing; Chen, Haicheng; Yao, Jiahui; Xie, Yun; Liang, Xiaoyan; Yang, Xing; Zhang, Min; Liu, Guihua (Frontiers in Pharmacology, 2021)
Triptolide is widely used in clinic treatment of various diseases. Side effects including reproductive toxicity to male patients limit its application. However no detailed mechanisms or potential intervention targets have been reported. In this study, we had shown that triptolide activated mitochondrial apoptosis pathway in rat testicular leydig cells and induced cell apoptosis both in vivo and in vitro, which may cause hypoleydigism and damage spermatogenesis. Mechanically, triptolide induced dynamin-related protein 1 (Drp1) over-expression, which interfered mitochondrial dynamic stability to activate mitochondrial apoptosis pathway. Mdivi-1, a selective Drp1 inhibitor, could partly reverse mitochondrial dynamic disturbance and rat testicular leydig cells’ apoptosis induced by triptolide. Inhibiting Drp1 over-activation may be a new strategy for mitigating the reproductive toxicity of triptolide.